In defense of food : an eater's manifesto - Pollan, Michael (Penguin Press, 2008)
"Eat food. Not too much. Mostly plants." These simple words go to the heart of food journalist Pollan's thesis. Humans used to know how to eat well, he argues, but the balanced dietary lessons that were once passed down through generations have been confused and distorted by food industry marketers, nutritional scientists, and journalists. As a result, we face today a complex culinary landscape dense with bad advice and foods that are not "real." Indeed, plain old eating is being replaced by an obsession with nutrition that is, paradoxically, ruining our health, not to mention our meals. Pollan's advice is: "Don't eat anything that your great-great grandmother would not recognize as food." Looking at what science does and does not know about diet and health, he proposes a new way to think about what to eat, informed by ecology and tradition rather than by the nutrient-by-nutrient approach.--From publisher description.